Role of Lectin in the Response of Aedes aegypti Against Bt Toxin - Alam, Intikhab; Batool, Khadija; Idris, Aisha Lawan; Tan, Weilong; Guan, Xiong; Zhang, Lingling (Frontiers in Immunology, 2022)
Aedes aegypti is one of the world’s most dangerous mosquitoes, and a vector of diseases such as dengue fever, chikungunya virus, yellow fever, and Zika virus disease. Currently, a major global challenge is the scarcity of antiviral medicine and vaccine for arboviruses. Bacillus thuringiensis var israelensis (Bti) toxins are used as biological mosquito control agents. Endotoxins, including Cry4Aa, Cry4Ba, Cry10Aa, Cry11Aa, and Cyt1Aa, are toxic to mosquitoes. Insect eradication by Cry toxin relies primarily on the interaction of cry toxins with key toxin receptors, such as aminopeptidase (APN), alkaline phosphatase (ALP), cadherin (CAD), and ATP-binding cassette transporters. The carbohydrate recognition domains (CRDs) of lectins and domains II and III of Cry toxins share similar structural folds, suggesting that midgut proteins, such as C-type lectins (CTLs), may interfere with interactions among Cry toxins and receptors by binding to both and alter Cry toxicity. In the present review, we summarize the functional role of C-type lectins in Ae. aegypti mosquitoes and the mechanism underlying the alteration of Cry toxin activity by CTLs. Furthermore, we outline future research directions on elucidating the Bti resistance mechanism. This study provides a basis for understanding Bti resistance, which can be used to develop novel insecticides.